Apolipoprotein B binds to enolase-1 and aggravates inflammation in rheumatoid arthritis. Issue 10 (11th July 2018) - Lee, Joo Youn; Kang, Min Jueng; Choi, Ji Yong; Park, Ji Soo; Park, Jin Kyun; Lee, Eun Young; Lee, Eun Bong; Pap, Thomas; Yi, Eugene C; Song, Yeong Wook
Abstract : Objective: Immune cells from patients with rheumatoid arthritis (RA) express more enolase-1 (ENO1) on their surface than those from healthy subjects, and they elicit an enhanced inflammatory response. This study is aimed to identify the ligands of ENO1 that could promote inflammatory loops in vitro and enhance the arthritis severity in vivo. Methods: ENO1-binding proteins in RA synovial fluid were identified by mass spectromety, and affinity to ENO1 was evaluated by means of a ligand blotting and binding assay, surface plasmon resonance and confocal microscopy. Proinflammatory response by the interaction between ENO1 and apolipoprotein B (apoB) was tested in vitro and in vivo using peripheral blood mononuclear cells and a K/BxN serum transfer arthritis model and low-density lipoproteins receptor (LDLR) knockout mice. Results: ApoB in the synovid fluid of patients with RA was identified as a specific ligand to ENO1 with a higher affinity than plasminogen, a known ENO1 ligand. ApoB binding to ENO1 on monocytes elicited the production of tumour necrosis factor-α, interleukins (IL)-1β and IL-6 through both p38 mitogen-activated protein kinase and NF-κB pathways. In the K/BxN serum transfer arthritis model, administration of apoB increased the production of proinflammatory cytokines and exaggerated arthritis severity. The severity of K/BxN serum transfer arthritis in LDLR knockout mice was comparable with wild-type mice. Conclusions: A key component of atherogenic lipids, apoB, aggravated arthritis by potentiating the inflammatory response via its interaction with ENO1 expressed on the surface of immune cells. This suggests a novel mechanism by which lipid metabolism regulates chronic inflammation in RA.